Risk Management in Business Planning X-ray Screening Detection System: Identification, Evaluation, and Mitigation Strategies - Sitinjak, Brando; Indradewa, Rhian; Nugroho, Sukmo Hadi; Kustiawan, Unggul (Innovative: Journal Of Social Science Research, 2025)
This study examines ISO 31000-based risk management at PT. CKK, an airport and port security X-Ray equipment repair service company regulated by ICAO, TSA, and BAPETEN. This qualitative study uses holistic case studies to assess the effectiveness of risk management frameworks in achieving short-term (reduced machine downtime <1% per month, SLAs <2 hours) and long-term (ASEAN expansion, IoT/AI adoption up to 80% of customers) business goals. The risk management approach includes risk identification (engine downtime with RPN=15 and bad debt collection with RPN=16), likelihood and impact matrix analysis, priority evaluation, risk handling, and Key Risk Indicators monitoring. The results reveal that integrating tailored, inclusive, and dynamic risk management principles with business goals reduced residual risk by 60–80% using IoT/AI for damage prediction and blockchain for supply chain transparency. Operations (29.4%) and marketing (27.9%) will account for most of the IDR 739.6 billion risk management cost in five years. These findings help similar organizations optimize risk management in the X-Ray-based security technology industry with rigorous restrictions and expand into the ASEAN regional market